Sacred groves: Traditional way of conserving plant diversity - Gaykar3, Vidya V. Shinde1*, D.A. Dhale2 and B.M. (Journal of Ecobiotechnology, 2011)
Sacred groves are the forest patches conserved by the local people intertwined with their sociocultural and religious practices. For the present study, Udhadavne sacred grove namely ‘Maruti Ban’ was selected and studied. Frequent visits were made and observations regarding floristic and ecological data were noted. Ethno botanical aspects of medicinal plants were studied. Some rare and endemic plant species were also noted. Totally 150 species of floristic plants were listed. It shows the richness in biodiversity of Udhadavne sacred grove. This sacred grove is specially conserved for tree species. Memecylon umbellatum and species of Ficus were found dominant. Some medicinal, endemic and rare plants were also protected accordingly. These observations indicate that the sacred groves are the traditional way of conserving plants.